Development of Highly Sensitive Glucose Sensor Based on Clustered Superparamagnetic Iron Oxide Nanoparticles - Choi Won Seok; Sungmin Han; Jaehong Key (대한의용생체공학회, 2019)
Superparamagnetic iron oxide nanoparticles (SPIONs) are used in a wide range of fields, such as contrast agents in magnetic resonance imaging and targeted drug delivery using the natural property that can move to a specific site in a magnetic field. It is also known to act as an artificial peroxidase that has a stable catalytic effect even a wide pH and temperature when compared with the natural peroxidase expressed in the body. Here, we have demonstrated a highly sensitive glucose sensor based on clustered SPIONs that coated with PLGA (Poly(lactic-co-glycolic acid)) via hydrophobic effect. We show that the clustered SPIONs have a higher sensitivity to glucose than the previous paper[1] that has discussed with just a single iron oxide core
Keywords: SPIONs; Glucose sensor; Nanoparticle; Clustering